2013
DOI: 10.3390/s130405109
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvement of the One-Dot Lateral Flow Immunoassay for Aflatoxin B1 by Using a Smartphone-Based Reading System

Abstract: This study was conducted to develop a simple, rapid, and accurate lateral flow immunoassay (LFIA) detection method for point-of-care diagnosis. The one-dot LFIA for aflatoxin B1 (AFB1) was based on the modified competitive binding format using competition between AFB1 and colloidal gold-AFB1-BSA conjugate for antibody binding sites in the test zone. A Smartphone-based reading system consisting of a Samsung Galaxy S2 Smartphone, a LFIA reader, and a Smartphone application for the image acquisition and data anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(52 citation statements)
references
References 12 publications
1
51
0
Order By: Relevance
“…Automating the S value calculation can be an alternative way of improving PAD sensitivity. Many previous studies have demonstrated the benefits of a smartphone for reading and obtaining a quantitative and objective result for an accurate diagnostic . For the first version of the PAD, an Android‐based application was developed on a smartphone for reproducible and quantitative results from the raw signals.…”
Section: Discussionmentioning
confidence: 99%
“…Automating the S value calculation can be an alternative way of improving PAD sensitivity. Many previous studies have demonstrated the benefits of a smartphone for reading and obtaining a quantitative and objective result for an accurate diagnostic . For the first version of the PAD, an Android‐based application was developed on a smartphone for reproducible and quantitative results from the raw signals.…”
Section: Discussionmentioning
confidence: 99%
“…It can greatly improve the automation of ELISA detection. Moreover, utilizing the sample flowing devices, multiplexed monitoring for immune assays can also be developed by lateral flow immunoassay (LFIA) based on smartphone (Lee et al, 2013;Yetisen et al, 2014;Yu et al, 2015;Zangheri et al, 2015). Besides immune assays, smartphone has also been used to capture chemiluminescence linked to redox reactions (Oncescu et al, 2013;Chun et al, 2014;Oncescu et al, 2014;Bueno et al, 2015).…”
Section: Colorimetric Biosensors On Smartphonementioning
confidence: 99%
“…The rapid methods currently under development allow the complete shift from qualitative ("yes/no") analysis to methods providing accurate quantitative data for simultaneous detection of several substances in complex mixtures and biolog ical fluids using portable readout and recording devices, with transmission of data through modern IT technologies. The development of new portable devices that allow the use of simple immunochro matographic systems to allow patients to conduct self diagnosis, process the results of the analysis using a conventional smartphone with special built in soft ware, or send the data to a specialized laboratory for further processing, diagnosis, and further medical advice, are very promising [53,54]. Undoubtedly, the research in this area will continue apace and lead in the near future to the development of simple, inexpen sive, portable biosensor devices suitable for mass and individual use.…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%